O fenômeno da preclusão : princípio, instituto e técnica na efetiva prestação da tutela jurisdicional - Amorim, Custódio Feitoza (2011)
This dissertation searches through the doctrine and jurisprudence in civil procedural law to demonstrate the importance of the phenomenon of the preclusion, the principle and its application as an effective technique in the process, the initial demand the ultimate in cognition of the Judiciary. It is analyzed as a phenomenon, principle and the theory Chiovenda Institute, comparing the different concepts in the Brazilian doctrine, especially with the inserts in comparative law, the preclusive time of the phenomenon. Through research on the jurisprudence of the Superior Courts is an evident application of the preclusion in the trial of a higher court, and ratio decidendi as precedents, both in quantitative as doctrinaire as the trial, which outweighs the phenomenon of the preclusion, composing the instrument process, in the delivery process effective judicial protection